Desiminasi Teknologi Domestikasi Ikan Putak (Notopterus notopterus) di Desa Putak, Kecamatan Gelumbang Kabupaten Muara Enim, Sumatera Selatan - Muslim, Muslim; Syaifudin, Mochamad; Taqwa, Ferdinand Hukuma; Oktarina, Selly (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Bronze featherback (Notopterus notopterus) is one of the fish species native to Indonesian waters. This species is closely related to the knifefish (Chitala sp.). South Sumatra uses this fish as a raw material for pempek and kemplang crackers. This fish has a high economic value like Chitala sp. The need for the culinary industry is increasing, causing the demand for this fish to also increase. Until now, the production of N. notopterus has relied on wild catches, as aquaculture production has not been available. Overfishing as well as habitat destruction have led to the decline of this species' population in the wild. Domestication is the effort to domesticate wild fish into a farming environment. The initial stage of N. notopterus domestication has been successfully carried out. They successfully survived and grew in aquaculture containers. This activity is the dissemination of information on the results of the initial stage of the N. notopterus domestication study. The methods used were counseling, demonstration plots, and mentoring. This activity was carried out in Putak Village, Gelumbang District, Muara Enim Regency. The results of the activity show that the community's knowledge of N. notopterus is increasing. People know that N. notopterus and Chitala hypselonotus are different species, even though they are very similar. Public awareness of the importance of preserving N. notopterus and Chitala hypselonotus is increasing. This activity is very beneficial for the Putak community.